2010
DOI: 10.1111/j.1365-2966.2010.17727.x
|View full text |Cite
|
Sign up to set email alerts
|

How does galaxy environment matter? The relationship between galaxy environments, colour and stellar mass at 0.4 < z < 1 in the Palomar/DEEP2 survey

Abstract: We present a study characterizing the environments of galaxies in the redshift range of 0.4 < z < 1 based on data from the POWIR near‐infrared imaging and DEEP2 spectroscopic redshift surveys, down to a stellar mass of log M*= 10.25 M⊙. Galaxy environments are measured in terms of nearest‐neighbour densities as well as fixed aperture densities and kinematical and dynamical parameters of neighbour galaxies within a radius of 1 h−1 Mpc. We disentangle the correlations between galaxy stellar mass, galaxy colour a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
71
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(80 citation statements)
references
References 80 publications
8
71
1
Order By: Relevance
“…This scenario is in agreement with findings based on large redshift surveys, which revealed an increasing environmental effect on galaxy evolution moving from higher to lower redshift, and from higher to lower galaxy stellar masses (Iovino et al 2010;Peng et al 2010;Grützbauch et al 2010).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This scenario is in agreement with findings based on large redshift surveys, which revealed an increasing environmental effect on galaxy evolution moving from higher to lower redshift, and from higher to lower galaxy stellar masses (Iovino et al 2010;Peng et al 2010;Grützbauch et al 2010).…”
Section: Discussionsupporting
confidence: 81%
“…They can suffer from tidal truncation (e.g., Rubin et al 1988) or tidal disruption (e.g., Oh et al 1995) during their orbit through a more massive dark matter halo, like a group or cluster of galaxies. Indeed, studies of the environmental influence on galaxy properties have found that the correlations between colour or star formation rate (SFR) and local galaxy density are the strongest for low-mass galaxies (Kauffmann et al 2004;Tasca et al 2009;Grützbauch et al 2010). Similarly, the morphology-density relation is very strong for low-mass galaxies (e.g., Binggeli et al 1990).…”
Section: Introductionmentioning
confidence: 99%
“…It is widely accepted in the literature that classical galaxy color/morphology trends in different environments are better investigated in bins of mass-volume-limited samples (Tasca et al 2009;Iovino et al 2010;Cucciati et al 2010;Kovač et al 2010;Xue et al 2010;Cooper et al 2010;Grützbauch et al 2011). This strategy enables one to break the degeneracy caused by the relationships between galaxy stellar masses and environment and between galaxy stellar masses and colors/morphologies.…”
Section: Datamentioning
confidence: 99%
“…The stellar mass estimates are tightly correlated to various other important global properties of galaxies (colour, metallicity, luminosity, environment, see e.g. Grützbauch et al 2011, and references therein) and they are therefore considered a useful tracer of the baryonic content of a galaxy.…”
Section: Introductionmentioning
confidence: 99%